2016
DOI: 10.1115/1.4032728
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Model for Carbonate Matrix Acidizing to Consider the Effects of Spent Acid

Abstract: Carbonate matrix acidizing is widely used in oil fields as a simple and easy method of production enhancement. However, the dissolution pattern created due to the reaction between the acid and the carbonates is a complex phenomenon. Several experimental and modeling studies have been carried out to simplify this process and design the optimum conditions for acidizing. One approach is to develop continuum models to simulate the dissolution process in the core scale. Conventional modeling approaches typically do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The most widely used one is the two-scale continuum model (TSC) developed by Panga et al [22] as it is advantageous at predicting the dissolution patterns observed in experiments and its accurate estimation of P V BT . For this reason, the TSC model is continuously extended to take into account the factors that affect the wormhole propagation [23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46]. For example, Kalia and Balakotaiah [23], and Cohen et al [24] extended the TSC model to the 2-D radial case by using the r − θ coordinates.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used one is the two-scale continuum model (TSC) developed by Panga et al [22] as it is advantageous at predicting the dissolution patterns observed in experiments and its accurate estimation of P V BT . For this reason, the TSC model is continuously extended to take into account the factors that affect the wormhole propagation [23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46]. For example, Kalia and Balakotaiah [23], and Cohen et al [24] extended the TSC model to the 2-D radial case by using the r − θ coordinates.…”
Section: Introductionmentioning
confidence: 99%
“…where ρ aq is density of electrolyte solution containing CO 2 (g/cm 3 ) and x CO 2 is mole fraction of CO 2 in the solution. We developed a new correlation based on the experimental data generated in this study (Equation (11)) to calculate density changes of CaCl 2 solution with addition of CO 2 :…”
Section: Co 2 -Cacl 2 -H 2 O Densitymentioning
confidence: 99%
“…In recent years, researchers have been paying attention to environmental issues such as CO 2 capture and geological storage in deep saline aquifers or depleted hydrocarbon reservoirs. However, the target depleted hydrocarbon reservoirs are mostly sandstone reservoirs [1][2][3][4][5][6]. Nevertheless, understanding thermodynamic behavior of this mixture is also important in flow enhancement, and well stimulation in petroleum production operations (i.e., matrix acidizing and acid fracturing) commonly used in carbonate reservoirs (i.e., limestone) are also a subject of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…Bastami et al (2014) investigated the thermodynamic behavior of the H 2 O-CaCl 2 -CO 2 system as products of acid-rock reaction, to estimate the solubility of carbon dioxide and free gas saturation. Bastami and Pourafshary (2016) developed a continuum model considering the acid consumption and the effect of reaction products, such as free gas, on the acid flow and the wormhole propagation. Bastami et al (2018) extended this work by considering a thermodynamic model to calculate the density of the H 2 O-CaCl 2 -CO 2 system.…”
Section: Introductionmentioning
confidence: 99%